Domain Analysis and Audit of IT Governance Based On COBIT 5 at Denpasar Industrial Training Center - Nyoman Putra Sastra; I Made Artana; Dewa Made Wiharta (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
Information technology has become a key element of organizations and one of institutions’ added value and competitive advantages. Therefore, IT must be properly managed and measured. Denpasar Industrial Training Center (BDI) has implemented the IT Governance Education and Training Information System, SISDIKLAT. These applications have never been evaluated from an IT governance perspective. This study aimed to determine domains and assess SISDIKLAT using methods relevant to COBIT 5. To assist the organization in focusing on its main objectives and strategies, a tailored governance system based on the specificities of SISDIKLAT is required. This research assist BDI Denpasar in establishing healthy governance and IT management by utilizing the COBIT 5 framework. Both qualitative and quantitative approaches are used to select relevant governance/management objectives. Four domains and nine subdomains were chosen based on the domain analysis. According to the assessment results, the capability value of each subdomain was 2–3, with a gap value of 0.2–0.8. To reach the target level, the nine subdomains were advised.